The Impact of Financial Inclusion towards Commercial Banks’ Profitability in Indonesia Listed in the IDX for the Year 2012 - 2017 - Rikky Prima; Kenny Natanael Tandra (iBuss Management, 2019)
Facing the low financial inclusion index in Indonesia, the government has been trying to push the commercial banks to help to expand the financial inclusion for the society. Although it is part of the banks’ responsibility to follow the governments’ issuance, there is no concrete evidence whether the movement is beneficial for the commercial banks. Facing such dilemma, the situation gives inspiration for the researchers to find out whether the financial inclusion provided by commercial banks in Indonesia from the supply side bring benefits to their performance.Data of 10 commercial banks in Indonesia from 2012 to 2017 were collected from each of their annual reports. In analyzing the data, the researchers use multiple linear regression analysis. The analysis regression results indicate that the number of ATMs significantly influence the ROAs and CIRs of commercial banks in Indonesia, while only the number of credit cards issued significantly influence the CIRs. Keywords:Financial inclusion, commercial banks, banks’ profitability, Indonesia, financial institutions